2014
DOI: 10.1152/ajpcell.00117.2013
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced endoplasmic reticulum SERCA activity by overexpression of hepatic stimulator substance gene prevents hepatic cells from ER stress-induced apoptosis

Abstract: An W. Enhanced endoplasmic reticulum SERCA activity by overexpression of hepatic stimulator substance gene prevents hepatic cells from ER stress-induced apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 57 publications
0
44
0
1
Order By: Relevance
“…www.impactjournals.com/oncotarget (PI3K) inhibitor, was used to block autophagy because the complex of Beclin-1 and PI3K is required for autophagic vesicle nucleation [17]. As reported in a previous study [18][19][20][21], less apoptotic cells were observed in mice treated with CCl 4 and ALR than those treated with CCl 4 only, which suggested that ALR inhibits hepatocyte apoptosis. 3-MA addition significantly promoted cell apoptosis in mice treated with CCl 4 and ALR, which indicated the inhibition of autophagy reverses the anti-apoptotic effect of ALR in acute liver injury ( Figure 5).…”
Section: Alr Suppresses Hepatocyte Apoptosis In Mice With CCL 4 -Indumentioning
confidence: 83%
“…www.impactjournals.com/oncotarget (PI3K) inhibitor, was used to block autophagy because the complex of Beclin-1 and PI3K is required for autophagic vesicle nucleation [17]. As reported in a previous study [18][19][20][21], less apoptotic cells were observed in mice treated with CCl 4 and ALR than those treated with CCl 4 only, which suggested that ALR inhibits hepatocyte apoptosis. 3-MA addition significantly promoted cell apoptosis in mice treated with CCl 4 and ALR, which indicated the inhibition of autophagy reverses the anti-apoptotic effect of ALR in acute liver injury ( Figure 5).…”
Section: Alr Suppresses Hepatocyte Apoptosis In Mice With CCL 4 -Indumentioning
confidence: 83%
“…Increased PC/PE ratio of the ER membrane leads to altered membrane fluidity which reduces SERCA2b function, resulting in decreased Ca 2+ accumulation in the ER lumen and impaired protein folding capacity (Fu et al, 2011). Similarly, two independent groups have recently shown that the incorporation of saturated fatty acids into the ER also reduces membrane fluidity and SERCA function, decreasing luminal ER Ca 2+ (Egnatchik et al, 2014; Zhang et al, 2014b). It has also been shown that modulation of LXRs regulates ER function through changes in membrane phospholipid composition and lipogenic and inflammatory responses (Rong et al, 2013).…”
Section: Liver Metabolism Function and Ca2+ Homeostasismentioning
confidence: 93%
“…Studies of cultured hepatocytes and hepatocellular carcinoma lines have revealed that exposure to excess saturated fatty acids in particular triggers cellular stress responses that can lead to cell death [9][10][11][12][13][14][15][16][17][18][19]. For these experiments, cells are typically incubated with palmitate (0.2 to 1.0 mM) conjugated to bovine serum albumin (BSA).…”
Section: Introductionmentioning
confidence: 99%